Prevention of Tuberculosis Transmission in Households Using Virgin Coconut Oil and Multi-Drug Treatment: A Quasi-Experimental Study - Najamuddin Andi Palancoi; Achmad Indra Awaluddin; Nur Syahrul Ramadhan; A. Nurul Khaerizza Safitri; St.Nurmiati Aminuddin (Jurnal Penelitian Pendidikan IPA, 2025)
The increasing prevalence and incidence of tuberculosis each year highlights the need to use Virgin Coconut Oil (VCO) in conjunction with multi-drug treatment to help suppress the transmission of tuberculosis within families. Lauric acid, the main component of VCO, transforms into monolaurin in the digestive tract. Monolaurin is a substance known to enhance the body's immune system. This study aimed to determine the effectiveness of Multi-drug Treatment and VCO treatment on Tuberculosis incidence in household contacts associated with cost effective analysis (CEA). This study employs a quasi-experimental method, a form of quantitative research akin to a true experiment but does not involve full randomisation of subjects or groups. Subjects were divided into two groups. The treatment group consisted of new tuberculosis patients who received a combination of multi-drug treatment and virgin coconut oil (VCO). Their household contacts were tested to determine whether they were positive for acid-fast bacilli at the initial stage and again at the second month of the study. The control group included new tuberculosis patients who received the Directly Observed Treatment Short Course (DOTS) or the multi-drug treatment (MDT) package only. Similar to the treatment group, their household contacts were also tested. After two months of treatment for tuberculosis among individuals in the same household, a follow-up showed significant differences between the intervention and control groups. In the intervention group, all 81 participants (100%) tested negative for acid-fast bacilli in the second month. In contrast, the control group had 3 participants (4.3%) who tested positive for acid-fast bacilli. The effectiveness of tuberculosis drug therapy is assessed by examining whether patients test negative for acid-fast bacilli during their second examination. The results indicate that patients receiving a combination of multi-drug treatment and VCO intervention have a higher rate of negative testing for acid-fast bacilli compared to those receiving only multi-drug treatment.